Pengembangan modul elektronik berbasis flipbook bertujuan meningkatkan kemampuan siswa dalam memecahkan masalah matematika pada topik bentuk akar - Sukmawati Dewi; Adiatama Adiatama; Pegi Idha Amarela (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to develop a flipbook-based electronic module as a learning aid to improve students' abilities in solving mathematical problems on the topic of root forms. This module development method follows a learning design approach that focuses on interactiveness and visualization of complex mathematical concepts. The research was conducted involving class XI students in a high school as test subjects. Data collection was carried out through tests of mathematical problem solving abilities before and after using the module, as well as structured interviews with mathematics teachers and students. The results showed that the use of a flipbook-based electronic module significantly improved students' understanding of the concept of root forms and their ability to solve related mathematical problems. The implication of this research is the importance of integrating technology in mathematics learning to improve effectiveness and student learning outcomes.